Implementation of Literacy Activities in the Equality Package A Program to Improve Reading Skills at Spnf Skb Negeri 2 Samarinda - Oktaviana, Elsya; Alisalman, Muhamad; Lukman, Andi Ismail; Setiawan, Ady (Journal of Educational Sciences, 2025)
This study aims to examine the implementation of literacy activities in the Equality Package A Program at SPNF SKB Negeri 2 Samarinda with a focus on the implementation of activities, the role and strategy of tutors, the obstacles faced, as well as support institutions and families in improving students' literacy skills. This study uses a qualitative approach with data collection techniques in the form of interviews, observations, and documentation studies. The results of the study show that the implementation of literacy at SPNF SKB Negeri 2 Samarinda is carried out through the provision of reading books, tutor training, and a plan to develop a Community Reading Park (TBM). Tutors play an important role as facilitators, motivators, and innovators by implementing creative strategies, such as storytelling, the use of image media, collaborative learning, and the use of digital games. The main obstacles that arise include limited reading facilities, heterogeneity of students' reading ability, fluctuations in learning motivation, and lack of support from family. In overcoming these obstacles, institutions prepare institutional strategies, tutors present a variety of learning methods, while parents provide assistance and motivation at home. This research emphasizes that the success of literacy in non-formal education is the result of synergy between institutions, tutors, students, and families. In addition, this research contributes to novelty by examining the implementation of literacy comprehensively through a multi-actor approach that has rarely been studied before, so that it can be a reference for the development of literacy programs in non-formal education pathways.